MAKNA FRASA INJIL ADALAH KEKUATAN ALLAH YANG MENYELAMATKAN SETIAP ORANG PERCAYA BERDASARKAN ROMA 1: 16-17 DAN APLIKASINYA BAGI ORANG PERCAYA MASA KINI - Aris D. Rimbe; Desiani; Tampilang, Petra Harys Alfredo (STT-RAI Batam, 2024)
This study examines the meaning of the phrase “the gospel is the power of God unto salvation” based on Romans 1:16-17 and its relevance for believers today. The background of this study is to provide a deep understanding of the gospel as a source of power that brings salvation to every believer, both Jews and Gentiles. The study utilizes a qualitative method with an expositional approach to the biblical text, supported by theological literature and commentaries from experts. The main objective of this study is to uncover how the gospel plays a role in strengthening, saving, and revealing God's truth, and how this understanding can be applied in the lives of believers today. The results show that the gospel is not only a message of salvation but also the power of God that actively works in the lives of believers. The application of this understanding for Christians today is the spirit to preach the gospel with conviction, live by faith, and entrust themselves completely to the power of God in every aspect of life.